Institutional determinants of tax buoyancy in developing nations / Munnaza Ashraf, Dr. Saima Sarwar - Ashraf, Munnaza; Sarwar, Saima (Faculty of Business and Management, Universiti Teknologi MARA Selangor, 2016)
This study was conducted to examine the role of institutions on tax buoyancy in a set of developing nations. The analysis of 50 nations from the time period 1996-2013 indicates that mostly institutional factors such as bureaucratic efficiency, rule of law, corruption are affecting negatively to the tax collection in these regions. Revenue from indirect taxes is more sensitive to these non-economic factors in a society. Moreover, the study suggests that nature of relationship between tax buoyancy and institutional characteristics of the system is sensitive to different categories of political regimes i.e. Democracy and Autocracy. Results showed that democracy is affecting positively to the tax collection while autocracy is having negative impact in each case i.e. direct, indirect or total tax revenues. But in autocratic regimes, proportion of indirect and direct taxes in total revenue is more than in case of democracy. Findings help to suggest that efforts should be made to democratize the political system mostly in developing world so that more and more tax revenue generation could be made possible.